Effect of Educational Guideline on Nurses Performance Regarding Postnatal Care of Mothers and Neonates - Samah Abd Elhaleim said; Hemmat Mostafe Elbana; Amira Mohammed Salama (SAGE Publishing, 2022)
Background Postnatal periods are very sensitive periods for both the mother and the neonates where morbidity and mortality are high. Post natal care knowledge has significant role in reducing such complications. The research aimed to determine the educational guideline's effect on nurses' performance regarding mothers and neonates' postnatal care. Design A quasi-experimental design was decided to fulfil the aim of this study. Setting The study was conducted in the obstetric skill lab of faculty of nursing, Benha university. Sample A purposive sample was used to recruit 140 maternity nurses from Maternal and child health centres at kalioubia governorate. data collection: Two tools were used: Tool (I) Structured Questionnaire sheet. It is composed of these parts: Part I: Socio-demographic characteristics and Part II: nurses' knowledge about postpartum care. Tool (II) postpartum care observation checklist. Results knowledge and practices about postpartum care showed highly statistically significant differences between pre and post- implementation phases, and total knowledge score regarding post-partum care were improved from 34.52% pre implementation to 45.65% after implementation with (t = 8.11 and p <0.01**) and total practice were improved from 38.52% pre implementation to 54.21% after implementation with highly significant difference (t = 12.75 and p < 0.01**). Conclusion Nurses' knowledge and practice show a significant improvement post-implementation of health educational guideline regarding the care of postnatal mothers and neonates compared to pre-implementation.